The roles of borders in two Polish films: In Heaven as it is on Earth (1996) and Yuma (2012) - Fajfer, Alicja (International Journal of Contemporary Economics and Administrative Sciences, 2016)
The aim of this paper is to analyse the images of the border in two Polish movies: Yuma (2012) and In Heaven as it is on Earth (1996). Although they belong to different genres, the border is a major theme in both films. This essay refers to the three points of interest concerning border movie analysis suggested by Dodds (2013), namely: the materiality of borders; different aspects of border crossings; and governance issues. His approach is combined with Lotman’s (1990) “boundary of a semiosphere”. The literature concerning American border cinema is also considered. It may be argued that both movies represent the understanding of borders in the current border studies agenda (Scott 2011). This means that they are shown as incoherent and mutually conflicting constructs.